The experiences and perceptions of people with chronic and rare diseases during political-economic sanctions in Iran: a qualitative study - Mohammad Mehdi Kiani; Hakimeh Mostafavi; Fatemeh Ebrahimi; Reza Majdzadeh; Efat Mohamadi; Alexander Kraemer; Alireza Olyaeemanesh; Amirhossein Takian (BMC, 2024)
Abstract Background Economic sanctions aim to exert pressure on political and economic foundations. Hypothesizing that sanctions might affect various aspects of population health, this study, as a component of a broader investigation to ascertain the trend effects of sanctions on selected health outcomes in Iran, seeks to explore the experiences of Iranian citizens associated with the imposed sanctions. Methods This is a qualitative study. We conducted 31 semi-structured interviews with randomly selected patients diagnosed with at least one chronic and rare disease from diverse backgrounds across four provinces in Iran. We analyzed data using an inductive content analysis approach, facilitated by the MAXQDA10 software. Results We identified three primary themes: direct effects, side effects, and coping strategies. The immediate effects were perceived to be manifested through the restriction of healthcare service availability and affordability for citizens. The side effects included the economic hardships experienced in individuals' lives and the perceived devastation caused by these difficulties. Some coping mechanisms adopted by patients or their families/relatives included prioritizing comorbidities, prioritizing health needs within families with multiple ill members, and readjusting health/illness requirements in light of daily living needs. Conclusion In addition to the inherent burden of their illness, patients faced substantial healthcare costs as a result of sanctions, restricted access to medications, and availability of low-quality medications. We advocate considering these challenges within the healthcare system resilience framework as a crucial first step for policymakers, aiming to determine actionable measures and mitigate the adverse effects of sanctions on citizens, particularly the most vulnerable groups.